Delving into the impact of cytogenetics and karyotyping on precise diagnosis and quality of life preservation in Pakistan (2011-2022) - Khan, Aftab Ahmad (International Journal of Pathology, 2024)
Introduction: Conventional cytogenetics or Karyotyping is an essential tool to examine the banded pattern of chromosomes during metaphase of the cell cycle. It helps in diagnosis of specific chromosomal abnormalities and clinical syndromes. We tried to find the prevalence of different cytogenetic abnormalities and significance of this technique. Methods: An observational, cross-sectional study with a focus on exploring the prevalence and significance of cytogenetic abnormalities was conducted during January 2011 and March 2022. This study was conducted at Islamabad Diagnostic Center, Islamabad, after approval from Ethical Committee. Patients were included who presented with clinical suspicion of genetic abnormalities. These abnormalities include those having mongoloid facies, gender ambiguities, primary amenorrhea (PA) in females, recurrent pregnancy loss (RPL) etc. Results: A total of 1703 patients were included who presented with clinical suspicion of genetic abnormalities. As a part of disorders of sex development (DSD), those who were registered as females, 21% turned out to be genetically male (46, XY), while 17.3% were found to be genetically females (46, XX). Those who presented with primary amenorrhea, 5.2% were genotypically male. 171 out of 186 children presented with clinical suspicion of having Down syndrome (DS) were having Trisomy 21. 45 known cases of hematological disorders like Aplastic Anemia (AA) were also analyzed for chromosomal breakage studies (characteristic of Fanconi Anemia, FA) by karyotyping. Out of these 26.6% were reported for having chromosomal breakages. 74% of those having myeloid hyperplasia showed Philadelphia chromosome (t (9; 22), confirming the diagnosis of Chronic Myeloid Leukemia (CML). Conclusion: Cytogenetic abnormalities are quite common but often remain undiagnosed due to unavailability of technical expertise needed for proper evaluation of different disorders. A multidisciplinary approach is needed for management and counseling of patients and their family members